2019
DOI: 10.1101/640938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small molecule inhibitors of G9a reactivate the maternal PWS genes in Prader-Willi-Syndrome patient derived neural stem cells and differentiated neurons

Abstract: Abstract/SummaryPatients with Prader-Willi-Syndrome (PWS) display intellectual impairment, hyperphagia, and various behavioral problems during childhood that converge on a neurologic deficit. The majority of PWS patients have genetic deletions of the paternal 15q11–q13 chromosomal region, with their maternal PWS locus intact but epigenetically silenced by hypermethylation and repressive histone modulation of the PWS imprinting center (PWS-IC). Inhibition of the euchromatin histone methyltransferase G9a by smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…These studies revealed that the inhibition of G9a leads to decrease in H3K9me2 marks but no changes to DNA methylation at the PWS-IC. A preprint from Wu et al confirmed the ability of G9a to activate maternal SNORD116 in neural progenitors and neurons derived from human PWS iPSCs [171]. These results probably indicate that G9a plays an important role in the establishment of DNA methylation at the PWS-IC but the activation of the maternal genes are dependent on the status of H3K9 methylation, independent of the PWS-IC DNA methylation.…”
Section: G9a and Glpmentioning
confidence: 82%
“…These studies revealed that the inhibition of G9a leads to decrease in H3K9me2 marks but no changes to DNA methylation at the PWS-IC. A preprint from Wu et al confirmed the ability of G9a to activate maternal SNORD116 in neural progenitors and neurons derived from human PWS iPSCs [171]. These results probably indicate that G9a plays an important role in the establishment of DNA methylation at the PWS-IC but the activation of the maternal genes are dependent on the status of H3K9 methylation, independent of the PWS-IC DNA methylation.…”
Section: G9a and Glpmentioning
confidence: 82%
“…Specifically, the histone H3 lysine 9 (H3K9) methyltransferase SETDB1 associates with the transcription factor ZNF274 bound to sites within the 5' cluster of SNORD116 repeats, resulting in the deposition of maternal-specific H3K9me3 marks ( Cruvinel et al, 2014 ). Knockdown or inhibition of either SETDB1 or ZNF274 was sufficient to induce a low level of SNORD116 transcript expression from the normally silent maternal allele ( Cruvinel et al, 2014 ; Wu et al, 2019 ; Langouët et al, 2020 ). Together, these results suggest some promise for possible epigenetic therapies that will be discussed at the end of this review.…”
Section: Epigenetic Mechanisms In Pwsmentioning
confidence: 99%